Mature Follicle Count and Multiple Gestation Risk Based on Patient Age in Intrauterine Insemination Cycles With Ovarian Stimulation. Issue 5 (May 2020) - Evans, M. Blake; Stentz, Natalie C.; Richter, Kevin S.; Schexnayder, Brian; Connell, Matt; Healy, Mae W.; Devine, Kate; Widra, Eric; Stillman, Robert; DeCherney, Alan H.; Hill, Micah J.
Abstract : OBJECTIVE: To estimate the risk of a multiple gestation pregnancy in ovarian stimulation intrauterine insemination (IUI) cycles when stratified by patient age and mature follicle number. METHODS: We conducted a retrospective cohort study at a single private practice fertility center of IUI cycles performed from 2004 to 2017. Intervention(s) were ovarian stimulation and IUI if postwash total motile sperm count was more than 8 million. Mature follicles were defined as 14 mm or more as measured on the day of ovulation trigger. Main outcomes and measures were rates of clinical pregnancy and multiple gestation. RESULTS: We identified 24, 649 women who underwent a total of 50, 473 IUI cycles. Increasing the number of mature follicles from one to five at the time of IUI in women younger than age 38 years increased the clinical pregnancy rate from 14.6% to 21.9% (adjusted odds ratio [aOR] 1.6, 95% CI 1.4–1.9), almost entirely from a marked increase in multiple gestations per cycle from 0.6% to 6.5% (aOR 9.9, 95% CI 6.9–14.2). There was little increase in singleton pregnancies per IUI (14.1–16.4%) regardless of mature follicle number. The per-pregnancy twin and higher-order multiple gestation risk significantly increased (3.9–23.3%, P <.01 and 0.2–10.6%, P <.01, respectively) when comparing one with five mature follicles present at the time of IUI ( P <.01). In women younger than age 38 years with more than three follicles present, more than one quarter of all pregnancies were multiples. Similar findings occurred in women aged 38–40 years. In women older than age 40 years, up to four follicles tripled the odds of pregnancy (aOR 3.1, 95% CI 2.1–4.5) while maintaining a less than 12% risk of multiple gestation per pregnancy and a 1.0% absolute risk of multiples. CONCLUSION: Caution should be used in proceeding with IUI after ovarian stimulation when there are more than two mature follicles in women younger than age 40 years owing to the substantially increased risk of multiple gestation without an improved chance of singleton clinical pregnancy. Abstract : Ovulation induction with more than two mature follicles in women younger than 40 years substantially increases the risk of multiple gestation without improved singleton rates.